2021
DOI: 10.3390/vaccines9101141
|View full text |Cite
|
Sign up to set email alerts
|

Sentiments Regarding COVID-19 Vaccination among Graduate Students in Singapore

Abstract: As the COVID-19 pandemic rages unabated, and with more infectious variants, vaccination may offer a way to transit out of strict restrictions on physical human interactions to curb the virus spread and prevent overwhelming the healthcare system. However, vaccine hesitancy threatens to significantly impact our progress towards achieving this. It is thus important to understand the sentiments regarding vaccination for different segments of the population to facilitate the development of effective strategies to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The passage of time as an indicator of certain harmful consequences (28%), distrust in the quality of the vaccine (23.4%), fear of side effects (13.7%) and distrust in the effectiveness of the vaccine (10.3%) were the main reasons for non-vaccination of Novi Sad students. The obtained results correspond to the findings of similar research which indicate that the speed of vaccine introduction, efficacy, side effects, side effects, safety and vaccine choice are the main reasons for variability among students around the world [11,12,32,36].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The passage of time as an indicator of certain harmful consequences (28%), distrust in the quality of the vaccine (23.4%), fear of side effects (13.7%) and distrust in the effectiveness of the vaccine (10.3%) were the main reasons for non-vaccination of Novi Sad students. The obtained results correspond to the findings of similar research which indicate that the speed of vaccine introduction, efficacy, side effects, side effects, safety and vaccine choice are the main reasons for variability among students around the world [11,12,32,36].…”
Section: Discussionsupporting
confidence: 88%
“…There is a slightly greater interest in student vaccination among students around the world compared to Serbia. Over 68% of postgraduate students at the University of Singapore [32], 76.3% of students from China [12], as many as 80% of Canadian public university students [11] and 81.6% of Italian university students [14] were ready to be vaccinated, as well as 89.4% of undergraduate students in India [33], while the Middle East is among the regions with the lowest vaccine acceptance rate in the world [34].…”
Section: Discussionmentioning
confidence: 99%
“…40 Other studies though have shown higher rates of vaccine update than seen in our study. Lim et al found that only 32% if graduate students expressed vaccine hesitancy, 66 with Riad et al ascertaining worldwide that only 13.9% of the dental students would reject the COVID-19 vaccine. 67 Barello et al also ascertained that 86.1% of the students in Italy would take the vaccine for COVID-19, with no significant difference between acceptance among healthcare students versus non-healthcare students.…”
Section: Discussionmentioning
confidence: 98%
“… 39 Lim et al studied vaccine acceptance in a university amongst students and found that many students were still hesistant to take vaccines. 44 …”
Section: Discussionmentioning
confidence: 99%